Aging Affects the Ability to Process the Optic Flow Stimulations: A Functional Near-Infrared Spectrometry Study. Issue 4 (3rd July 2020) - Hinderaker, Mark; Sylcott, Brian; Williams, Keith; Lin, Chia-Cheng
Abstract: Optic flow (OF) has been utilized to investigate the sensory integration of visual stimuli during postural control. It is little known how the OF speed affects the aging brain during the sensory integration process of postural control. This study was to examine the effect of OF speeds on the brain activation using functional near-infrared spectroscopy (fNIRS) and postural sway between younger and older adults. Eleven healthy younger adults (5M/6F, age 22 ± 1-year-old) and ten healthy older adults (4M/6F, age 71 ± 5-year-old) participated in this study. A virtual reality headset was used to provide the OF stimulus at different speeds. A forceplate was used to record the center-of-pressure to compute the amplitude of postural sway (peak-to-peak). Compared with younger adults, older adults showed significantly increased activation in the OF speed of 10 m/s and decreased activation in the OF speed of 20 m/s in the left dorsolateral prefrontal cortex. Older adults also showed decreased activation in the left temporoparietal region (VEST) in the OF speed of 20 m/s. A significant difference in peak-to-peak was found between groups. Our results indicated that age might be associated with the ability to process fast OF stimulation.